Handbook of flow visualization - Yang, Wen-Jei (Taylor & Francis, 2001)
Compiles major techniques of flow visualization and demonstrates their applications in various fields of science and technology. This book includes a chapter that covers flow visualization applications in large wide tunnels for airplane and automobile testing.